2011
DOI: 10.1063/1.3562832
|View full text |Cite
|
Sign up to set email alerts
|

Atom—Diatom Collision Processes: Rovibrationally Detailed Cross Sections For Models

Abstract: Abstract. Atom-diatomic molecule collision processes are of particular importance in nonequilibrium numerical models in which rovibrational energy exchange and state-selected dissociation are taken into account by means of rate coefficients. If also translational nonequilibrium is considered, availability of large sets of cross sections is needed. To cope with this issue extended quasiclassical calculations have been performed to obtain translational energy dependent detailed data for hydrogen, nitrogen and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Bose et al 8 extended the temperature range of reaction 1 to 14,000 K and analyzed the relationship between the rate coefficient and the vibrational energy levels ν in the range of 0−15. Sayoś et al 19 studied the forward and backward reactions using a variational transition-state theory with a microcanonical optimized multidimensional tunneling correction, which agreed well with the experimental data in the temperature range of 300− 5000 K. He et al 20 calculated the thermal rate coefficients of reaction 1 at translational temperatures of 300−10000 Esposito et al 21 used a quasi-classical method to study the relationship between the rovibrational state of the O 2 molecule and the variation of the relative energy of the scattering cross section with v = 0 and j = 1. Mankodi et al 22 reported the exchange cross section (ECS) and dissociation cross section of reaction 1 on the 2 A′ and 4 A′ PESs using the PES proposed by Sayoś et al Baulch et al 23 gave an expression for the rate of reaction 1 in the temperature range of 298−5000 K using the three-parameter Arrhenius equation: k(T) = 1.5 × 10 −14 T exp(−3270/T) cm 3 mol −1 s −1 ; the fitting error of this expression is Δlog k = ±0.12in the temperature range of 298−1000 K and Δlog k = ±0.3in the temperature range of 1000−5000 K, which is considered to be the best representation of the experimental data so far.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Bose et al 8 extended the temperature range of reaction 1 to 14,000 K and analyzed the relationship between the rate coefficient and the vibrational energy levels ν in the range of 0−15. Sayoś et al 19 studied the forward and backward reactions using a variational transition-state theory with a microcanonical optimized multidimensional tunneling correction, which agreed well with the experimental data in the temperature range of 300− 5000 K. He et al 20 calculated the thermal rate coefficients of reaction 1 at translational temperatures of 300−10000 Esposito et al 21 used a quasi-classical method to study the relationship between the rovibrational state of the O 2 molecule and the variation of the relative energy of the scattering cross section with v = 0 and j = 1. Mankodi et al 22 reported the exchange cross section (ECS) and dissociation cross section of reaction 1 on the 2 A′ and 4 A′ PESs using the PES proposed by Sayoś et al Baulch et al 23 gave an expression for the rate of reaction 1 in the temperature range of 298−5000 K using the three-parameter Arrhenius equation: k(T) = 1.5 × 10 −14 T exp(−3270/T) cm 3 mol −1 s −1 ; the fitting error of this expression is Δlog k = ±0.12in the temperature range of 298−1000 K and Δlog k = ±0.3in the temperature range of 1000−5000 K, which is considered to be the best representation of the experimental data so far.…”
Section: Introductionmentioning
confidence: 63%
“…Bose et al extended the temperature range of reaction to 14,000 K and analyzed the relationship between the rate coefficient and the vibrational energy levels ν in the range of 0–15. Sayós et al studied the forward and backward reactions using a variational transition-state theory with a microcanonical optimized multidimensional tunneling correction, which agreed well with the experimental data in the temperature range of 300–5000 K. He et al calculated the thermal rate coefficients of reaction at translational temperatures of 300–10000 Esposito et al used a quasi-classical method to study the relationship between the rovibrational state of the O 2 molecule and the variation of the relative energy of the scattering cross section with v = 0 and j = 1. Mankodi et al .…”
Section: Introductionmentioning
confidence: 69%